Pengaruh Intervensi Gym Ball Exercise Dan Neyromuscular Taping Mengurangi Skala Nyeri Pada Pasien Low Back Pain (LBP) Myogenik - Yose Rizal (Jurnal Ilmiah Fisioterapi, 2022)
Low Back Pain (LBP) Miogenic is pain around the lower back that arises due to disturbances or abnormalities in the musculoskeletal elements without being accompanied by neurological disorders. Low Back Pain (LBP) Miogenic related to excessive daily activities, heavy weight lifting, standing too long or sitting in the wrong position. The purpose of this study was to determine the effect of Gym Ball Exercise (GBE) and Neuromuscular Taping (NMT) interventions in reducing pain scale in Myogenic Low Back Pain (LBP) patients. This study uses a Quasi Experimental method with One group pre-test and post-test design. The sample of this study amounted to 18 patients who performed physiotherapy. Data analysis using Wilcoxon Statistical Test. Based on the analysis, it was found that there was a significant change in the patient's pain score before and after physiotherapy (P<0.001) so it was concluded that the administration of Gym Ball Exercise (GBE) and Neuromuscular Taping (NMT) was effective in reducing the pain scale of patients with Low Back Pain (P<0.001). LBP) Miogenic. From the results of this study, giving Gym Ball Exercise (GBE) and Neuromuscular Taping (NMT) can be an alternative in the implementation of physiotherapy in patients with Miogenic Low Back Pain (LBP). Keywords : Low Back Pain (LBP) Miogenic, Pain, Gym Ball Exercise (GBE), Neuromuscular Taping (NMT